Grain boundary diffusion method of high-performance sintered neodymium-iron-boron magnet

By using laser pulse deposition technology to build grain boundary diffusion channels on the surface of sintered NdFeB magnets and diffuse heavy rare earth elements deeply, the problem of insufficient diffusion depth of heavy rare earths is solved, and the high-temperature magnetic performance and coercivity of the magnet are significantly improved.

CN119480311AActive Publication Date: 2025-02-18JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD

Patent Information

Application Number
CN202411389119.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the prior art, the diffusion depth of heavy rare earth elements in the sintered neodymium iron boron magnet is insufficient, resulting in a decrease in magnetic properties at high temperatures, and heavy rare earths may diffuse to the main phase, reducing residual magnetism and coercivity.

Method used

Laser pulse deposition technology is used to uniformly sputter non-rare earth metals or metal oxides on the surface of presintered NdFeB magnets to build grain boundary diffusion channels, and sputter heavy rare earth alloys through multiple laser pulse deposition techniques to diffuse deeply into the magnet.

Benefits of technology

It effectively avoids the accumulation of heavy rare earth elements on the magnet surface, improves the diffusion depth of heavy rare earth elements in the magnet, improves the high-temperature magnetic performance of sintered NdFeB magnets, and enhances coercivity and squareness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480311A_ABST
    Figure CN119480311A_ABST
Patent Text Reader

Abstract

The invention discloses a grain boundary diffusion method of a high-performance sintered neodymium-iron-boron magnet. The preparation method comprises the following steps: sequentially carrying out hydrogen decrepitation, jet milling, magnetic field forming, cold isostatic pressing and low-temperature presintering treatment on a neodymium-iron-boron alloy rapid hardening sheet to obtain a presintered neodymium-iron-boron magnet; depositing a non-rare earth metal or metal oxide film layer on the surface of the pre-sintered magnet by using a pulse laser deposition process; performing diffusion heat treatment on the neodymium-iron-boron magnet deposited with the non-rare earth metal or metal oxide film layer; depositing a heavy rare earth element film layer on the surface of the treated neodymium-iron-boron magnet by using the pulse laser deposition process again; and performing diffusion heat treatment and tempering treatment on the treated neodymium-iron-boron magnet. According to the method, the diffusion cost is reduced, meanwhile, the diffusion depth of heavy rare earth elements in the magnet is increased, the neodymium-iron-boron magnet with high coercive force and high magnetic energy product is prepared, and the urgent application requirements of emerging industries such as rare earth permanent magnet motors are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a grain boundary diffusion method for a high-performance sintered NdFeB magnet. Background Art

[0002] The third generation of permanent magnet material sintered NdFeB magnet is a high-performance permanent magnet material, which is widely used in many fields such as electronics, motors, medical equipment, automobiles, etc. With the expansion of application fields, the performance requirements for sintered NdFeB magnets are getting higher and higher. Due to the low Curie temperature of sintered NdFeB magnets, the magnetic properties drop sharply in a high temperature working environment, which seriously affects normal use.

[0003] At present, diffusing heavy rare earth elements into sintered NdFeB magnets through grain boundary diffusion technology is one of the most commonly used methods to improve the magnetic properties of sintered NdFeB magnets at high temperatures. Grain boundary diffusion technology can greatly improve the coercive force of magnets, and the amount of heavy rare earth used is very low, which reduces the cost of heavy rare earth raw materials. However, during the diffusion process of heavy rare earth elements, heavy rare earths accumulate on the surface of the magnet and the diffusion depth is insufficient. Moreover, heavy rare earths may diffuse into the main phase, resulting in a decrease in the remanence of the magnet after diffusion and insufficient coercive force increment. Therefore, how to better improve the diffusion effect of sintered NdFeB magnets is particularly critical. Summary of the invention

[0004] The purpose of the present invention is to provide a grain boundary diffusion method for high-performance sintered NdFeB magnets, aiming to solve the problem of accumulation of heavy rare earth elements on the surface of magnets, increase the diffusion depth of heavy rare earth elements in magnets, and prepare high-performance sintered NdFeB grain boundary diffusion magnets.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a grain boundary diffusion method for high-performance sintered NdFeB magnets, the grain boundary diffusion method specifically comprises the following steps:

[0006] S1) subjecting the NdFeB alloy quick-solidification sheet to hydrogen crushing, air flow grinding, magnetic field forming, cold isostatic pressing and low-temperature pre-sintering treatment in sequence to obtain a pre-sintered NdFeB magnet;

[0007] S2) placing the NdFeB magnet obtained by the treatment in S1) into a vacuum chamber and heating it, and then evenly sputtering the non-rare earth metal or metal oxide onto the surface of the NdFeB magnet by laser pulse deposition technology;

[0008] S3) performing sintering and tempering process on the pre-sintered NdFeB magnet obtained by the process in S2);

[0009] S4) placing the NdFeB magnet obtained by the treatment in S3) into a vacuum chamber and heating it, and then evenly sputtering a heavy rare earth alloy target onto the surface of the NdFeB magnet using a laser pulse deposition technique;

[0010] S5) subjecting the NdFeB magnet obtained after the treatment in S4) to sintering and tempering processes, that is, completing the grain boundary diffusion of the high-performance sintered NdFeB magnet.

[0011] Further, the specific steps of S2) are:

[0012] S2.1) first fill the vacuum chamber with pure argon gas at a pressure of 1-5 Pa, and heat the pre-sintered NdFeB magnet obtained in S1) to a temperature of 900-1000°C;

[0013] S2.2) The target material is uniformly sputtered onto the surface of a pre-sintered NdFeB magnet rotating at a speed of 1 to 100 rpm using a laser pulse deposition technique.

[0014] Furthermore, the specific process of the laser pulse deposition technology in S2.2) is as follows: the laser energy density is 1 to 10 J / cm 2 , the laser frequency is 1 to 10 Hz, and the laser pulse deposition time is 1 to 100 minutes.

[0015] Furthermore, the target material in S2.2) is a non-rare earth metal or a metal oxide; the non-rare earth metal is one or more combinations of Cu, Al, Mg, Ni, and Zn; the metal oxide is one or more combinations of MgO and ZnO.

[0016] Furthermore, the sintering temperature in S3) is 1000-1200°C for 4-48 hours; the tempering temperature is 400-600°C for 1-8 hours.

[0017] Furthermore, in said S4), the vacuum chamber is filled with pure argon gas, the gas pressure is 1-5 Pa, and the heating temperature is 900-1000°C.

[0018] Furthermore, the process parameters of the laser pulse deposition technology in S4) are: laser energy density is 1 to 10 J / cm 2 , the laser frequency is 1 to 10 Hz, and the laser pulse deposition time is 1 to 100 minutes.

[0019] Further, the heavy rare earth alloy target material in S4) has a composition of RE x (Ho a Tm 1-a ) y M 1-x-y , wherein RE is one or more combinations of Dy, Tb, and Gd, M is one or more combinations of Fe, Al, Ga, and Cu, 0≤a≤0.1at.%, and 0.5≤x≤0.9at.%, is 0≤y≤0.1at.%.

[0020] Furthermore, the coercive force increase of the high-performance sintered NdFeB magnet treated by the grain boundary diffusion method is not less than 12 kOe, and the squareness is not less than 0.95.

[0021] A high-performance sintered NdFeB magnet is prepared by the above-mentioned preparation method.

[0022] The beneficial effects of the present invention are as follows: by adopting the above technical scheme, the grain boundary diffusion method of the present invention reduces the raw material cost and the production cost, and effectively avoids the accumulation of heavy rare earth elements on the surface of the magnet, increases the diffusion depth of the heavy rare earth elements in the magnet, and prepares a sintered NdFeB magnet with both high coercive force and high squareness. The operation is simple and easy, and it is convenient for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flowchart of a grain boundary diffusion method for high performance sintered NdFeB magnets. DETAILED DESCRIPTION

[0024] The present invention will be further illustrated below in conjunction with examples and comparative examples. It should be understood that the following specific embodiments are only used to illustrate the features and advantages of the present invention, and are not used to limit the scope of the present invention.

[0025] like Figure 1 As shown, the present invention provides a grain boundary diffusion method for high-performance sintered NdFeB magnets, and the specific preparation process is as follows:

[0026] Step 1: Smelt the NdFeB alloy raw material and spin it into sheets to obtain quick-setting sheets.

[0027] Specifically, the chemical formula of NdFeB raw material composition is RE x M y B z Fe bal. ; wherein RE is one or more combinations of Pr, Nd, La, and Ce elements, M is one or more combinations of Al, Cu, Ga, Zr, Ni, Zn, and Sn elements, x is 28 to 33 wt.%, y is 0.5 to 5.5 wt.%, and z is 0.85 to 1.2 wt.%.

[0028] The NdFeB quick-setting sheet alloy described in the present application is prepared by a quick-setting furnace, and the quick-setting sheet has a thickness of 200 to 350 μm.

[0029] Step 2: The NdFeB alloy quick-solidification sheet is subjected to hydrogen crushing, air flow grinding, magnetic field forming, and cold isostatic pressing in sequence to obtain a NdFeB magnet green body.

[0030] Specifically, the grinding pressure of the jet mill is set to 520-620 kPa, and the speed of the separation wheel is 4000-5600 rpm. The magnetic field forming size is 30×16×13 mm3 , density is 3.8~4.1g / cm 3 The maximum pressure of cold isostatic pressing is 200MPa, the holding time is 1 to 5mins, and the density of the blank after isostatic pressing is 4.4 to 4.6g / cm 3 .

[0031] Step 3: The green body obtained in step 2 is pre-sintered at a low temperature to obtain a semi-dense pre-sintered magnet containing a rare earth-rich grain boundary phase with wide spacing and uniform distribution.

[0032] Specifically, the low-temperature pre-sintering temperature is 700-900°C, the holding time is 1-3h, and the pre-sintering pressure is <5×10 -3 Pa, the generated rare earth-rich grain boundary phase is distributed in a network in the semi-dense magnet, and the phase composition is (Pr a Nd 1-a ) x (La b Ce 1-b ) y M 1-x-y , x is 55-80 at.%, y is 0-35 at.%; in particular, a is 0-80 at.%, b is 0-60 at.%, and M is one or more combinations of Al, Cu, and Ga.

[0033] Step 4: The pre-sintered magnet obtained in step 4 is used as a diffusion substrate, heated, and a non-rare earth metal or metal oxide film layer is deposited on the surface of the pre-sintered magnet using a pulsed laser deposition process.

[0034] Specifically, the size of the pre-sintered magnet used as the diffusion substrate is φ10×10mm 3 ; The diffusion source is a non-rare earth metal or metal oxide, and its composition is one or more combinations of Cu, Al, Mg, Ni, Zn, MgO, and ZnO.

[0035] Step 5: The coated blank obtained in step 4 is subjected to diffusion heat treatment, followed by sintering and tempering processes to obtain a grain boundary diffusion sintered NdFeB magnet.

[0036] Specifically, the temperature for grain boundary diffusion of the pre-sintered magnet is 800-1000°C, and the time is 4-24h; the sintering temperature is 1050-1200°C, and the time is 1-12h; the primary tempering temperature is 750-980°C, and the time is 1-6h; the secondary tempering temperature is 450-650°C, and the time is 1-6h.

[0037] Step 6: Using the magnet obtained in step 5 as a diffusion substrate, heat it, and use a pulsed laser deposition process to deposit a heavy rare earth element film layer on the surface of the pre-sintered magnet.

[0038] Specifically, the diffusion source is a heavy rare earth alloy with a composition of RE x (Ho a Tm 1-a ) y M 1-x-y (at.%), wherein RE is one or more combinations of Dy, Tb, Gd, M is one or more combinations of Fe, Al, Ga, Cu, 0≤a≤10, and 50≤x≤90, which is 0≤y≤10.

[0039] Step 7: The coated blank obtained in step 6 is subjected to diffusion heat treatment, and then subjected to a tempering process to obtain a grain boundary diffusion high coercivity sintered NdFeB magnet.

[0040] Specifically, the primary tempering temperature of the magnet is 750-980° C., and the time is 1-6 hours; the secondary tempering temperature is 450-650° C., and the time is 1-6 hours.

[0041] The present invention is described in detail below with reference to several specific embodiments.

[0042] Example 1

[0043] Prepared by rapid setting furnace with nominal composition (PrNd) 29 Al 0.1 Cu 0.2 Co 0.2 Zr 0.2 B 0.9 Fe bal. (wt.%) quick-setting sheet. The thickness of the quick-setting sheet is controlled at 200-350μm. The quick-setting sheet is placed in a rotary heat treatment furnace for heat treatment, and then hydrogen crushing treatment is carried out in the rotary heat treatment furnace. The pre-diffusion temperature is 600℃, the pre-diffusion time is 6h, the hydrogen absorption pressure is 0.1MPa, the hydrogen absorption time is 0.5h, the dehydrogenation temperature is 540℃, and the dehydrogenation time is 3h. Subsequently, 0.08wt.% of antioxidant is added to the hydrogen crushing powder, and the powder is mixed for 3h under nitrogen protection; the mixed hydrogen crushing powder is further refined to 2.5-3.5μm in a jet mill; wherein the grinding pressure of the jet mill is set to 580kPa, and the speed of the sorting wheel is set to 5500rpm. 0.05wt.% of lubricant is added to the fine powder prepared by the jet mill, and the powder is mixed for 3h under nitrogen protection; the fine powder is oriented and formed in a magnetic field forming press to prepare a blank with a size of 30×16×13mm 3 , density is 3.8~4.1g / cm 3 Subsequently, the pressed green sheet was further compacted in a cold isostatic pressing device with a maximum pressure of 200 MPa and a holding time of 5 min. The density of the green sheet after isostatic pressing was 4.4-4.6 g / cm 3The green body was pre-sintered at 800°C for 1 h at a pre-sintering pressure of <5×10 -3 The obtained pre-sintered magnet is used as a substrate, and non-rare earth metals or metal oxides are selected as diffusion sources for laser pulse deposition; specifically, the size of the pre-sintered magnet used as the diffusion substrate is φ10×10mm 3 The laser pulse deposition was performed in an argon atmosphere with a laser energy density of 2 J / cm2. 2 , the laser frequency is 5Hz, and the laser pulse deposition time is 10mins. Subsequently, the deposited pre-sintered magnet is directly subjected to grain boundary diffusion, followed by sintering and tempering processes; specifically, the temperature for grain boundary diffusion of the pre-sintered magnet is 900℃, and the time is 10h; the sintering temperature is 1080℃, and the time is 4h. The obtained magnet is used as the substrate, and a heavy rare earth alloy is selected as the diffusion source for laser pulse deposition; specifically, the size of the pre-sintered magnet used as the diffusion substrate is φ10×10mm 3 , rotate at 10 rpm, and select the composition as Dy 78 Al 22 As a diffusion source, laser pulse deposition was used to sputter perpendicular to the c-axis in an argon environment. The laser energy density used for laser pulse deposition was 5 J / cm 2 , the laser frequency is 10Hz, and the laser pulse deposition time is 10mins. Subsequently, the deposited pre-sintered magnet is directly subjected to grain boundary diffusion, followed by sintering and tempering processes; specifically, the temperature for grain boundary diffusion of the magnet is 900℃, and the time is 10h; the sintering temperature is 1080℃, and the time is 4h; the primary tempering temperature is 900℃, and the time is 2h; the secondary tempering temperature is 500℃, and the time is 2h.

[0044] Comparative Example 1

[0045] Prepared by rapid setting furnace with nominal composition (PrNd) 29 Al 0.1 Cu 0.2 Co 0.2 Zr 0.2 B 0.9 Fe bal.(wt.%) quick-setting sheet. The thickness of the quick-setting sheet is controlled at 200-350μm. The quick-setting sheet is placed in a rotary heat treatment furnace for heat treatment, and then hydrogen crushing treatment is carried out in the rotary heat treatment furnace. The pre-diffusion temperature is 600℃, the pre-diffusion time is 6h, the hydrogen absorption pressure is 0.1MPa, the hydrogen absorption time is 0.5h, the dehydrogenation temperature is 540℃, and the dehydrogenation time is 3h. Subsequently, 0.08wt.% of antioxidant is added to the hydrogen crushing powder, and the powder is mixed for 3h under nitrogen protection; the mixed hydrogen crushing powder is further refined to 2.5-3.5μm in a jet mill; wherein the grinding pressure of the jet mill is set to 580kPa, and the speed of the sorting wheel is set to 5500rpm. 0.05wt.% of lubricant is added to the fine powder prepared by the jet mill, and the powder is mixed for 3h under nitrogen protection; the fine powder is oriented and formed in a magnetic field forming press to prepare a blank with a size of 30×16×13mm 3 , density is 3.8~4.1g / cm 3 Subsequently, the pressed green sheet was further compacted in a cold isostatic pressing device with a maximum pressure of 200 MPa and a holding time of 5 min. The density of the green sheet after isostatic pressing was 4.4-4.6 g / cm 3 The green body was pre-sintered at 800°C for 1 h at a pre-sintering pressure of <5×10 -3 The obtained pre-sintered magnet is used as a substrate to undergo sintering and tempering processes; specifically, the sintering temperature is 1080°C for 8 hours; the primary tempering temperature is 900°C for 2 hours; and the secondary tempering temperature is 500°C for 2 hours.

[0046] Example 2

[0047] The same quick-setting sheet with the same composition and the same preparation process as in Example 1 is used, the only difference being that the step of selecting non-rare earth metals or metal oxides as diffusion sources for laser pulse deposition is omitted.

[0048] Example 3

[0049] The same quick-setting sheet with the same composition and the same preparation process as in Example 1 is used, the only difference being that the step of selecting a heavy rare earth alloy as a diffusion source for laser pulse deposition is omitted.

[0050] The magnets prepared in the above examples and their comparative examples were subjected to room temperature (20° C.) magnetic performance tests using a permanent magnetic material measurement system. The performance results are shown in Table 1 below.

[0051] Table 1 Comparison of magnet performance parameters in the embodiments and comparative examples

[0052]

[0053] Comparing the magnetic performance data of Example 1 and Comparative Example 1, it is found that the coercive force (H cj ), squareness (H k / H cj ) and the maximum magnetic energy product ((BH)max) are significantly higher than those of the comparative example. Further, by comparing the magnetic properties data of Examples 2 to 3, the magnetic properties of Example 1 are better than those of Examples 2 and 3. It can be seen that by using laser pulse deposition technology to first diffuse non-rare earth metals or metal oxides in the pre-sintered magnet to construct a grain boundary diffusion channel, and then directly subjecting it to grain boundary diffusion treatment, the accumulation of heavy rare earth elements on the surface of the magnet can be effectively avoided, the diffusion depth of heavy rare earth elements in the magnet is increased, and a sintered NdFeB grain boundary diffusion magnet with both high coercivity and high squareness is obtained.

[0054] The invention discloses a grain boundary diffusion method for a high-performance sintered NdFeB magnet. A grain boundary diffusion channel is constructed in a pre-sintered magnet, and then the pre-sintered magnet is directly subjected to grain boundary diffusion treatment, followed by sintering and tempering processes, so that the accumulation of heavy rare earth elements on the surface of the magnet is effectively avoided, and the diffusion depth of the heavy rare earth elements in the magnet is increased, thereby obtaining a sintered NdFeB grain boundary diffusion magnet with both high coercivity and high squareness, which has important guiding significance.

[0055] The above is a detailed introduction to the grain boundary diffusion method of a high-performance sintered NdFeB magnet provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of ​​the present application; at the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

[0056] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.

[0057] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0058] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0059] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.

Claims

1. A grain boundary diffusion method for high performance sintered NdFeB magnets, characterized in that: The grain boundary diffusion method specifically comprises the following steps: S1) subjecting the NdFeB alloy quick-solidification sheet to hydrogen crushing, air flow grinding, magnetic field forming, cold isostatic pressing and low-temperature pre-sintering treatment in sequence to obtain a pre-sintered NdFeB magnet; S2) placing the pre-sintered NdFeB magnet obtained in S1) into a vacuum chamber and heating it, and then uniformly sputtering a non-rare earth metal or metal oxide target onto the surface of the NdFeB magnet using a laser pulse deposition technique; S3) performing sintering and tempering process on the pre-sintered NdFeB magnet obtained by the process in S2); S4) placing the NdFeB magnet obtained by the process in S3) into a vacuum chamber and heating it, and then evenly sputtering a heavy rare earth alloy target onto the surface of the NdFeB magnet by laser pulse deposition technology; S5) subjecting the NdFeB magnet obtained after the treatment in S4) to sintering and tempering processes, that is, completing the grain boundary diffusion of the high-performance sintered NdFeB magnet.

2. The grain boundary diffusion method according to claim 1, characterized in that: The specific steps of S2) are: S2.1) first fill the vacuum chamber with pure argon gas at a pressure of 1-5 Pa, and heat the pre-sintered NdFeB magnet obtained in S1) to a temperature of 900-1000°C; S2.2) The target material is uniformly sputtered onto the surface of a pre-sintered NdFeB magnet rotating at a speed of 1 to 100 rpm using a laser pulse deposition technique.

3. The grain boundary diffusion method according to claim 2, characterized in that: The specific process of the laser pulse deposition technology in S2.2) is: the laser energy density is 1 to 10 J / cm 2 , the laser frequency is 1 to 10 Hz, and the laser pulse deposition time is 1 to 100 minutes.

4. The grain boundary diffusion method according to claim 2, characterized in that: The target material in S2.2) is a non-rare earth metal or a metal oxide; the non-rare earth metal is one or more combinations of Cu, Al, Mg, Ni, and Zn; the metal oxide is one or more combinations of MgO and ZnO.

5. The grain boundary diffusion method according to claim 1, characterized in that: The sintering temperature in S3) is 1000-1200°C for 4-48 hours; the tempering temperature is 400-600°C for 1-8 hours.

6. The grain boundary diffusion method according to claim 1, characterized in that: In the step S4), the vacuum chamber is filled with pure argon gas, the gas pressure is 1-5 Pa, and the heating temperature is 900-1000°C.

7. The grain boundary diffusion method according to claim 1, characterized in that: The process parameters of the laser pulse deposition technology in S4) are: laser energy density is 1-10 J / cm 2 , the laser frequency is 1 to 10 Hz, and the laser pulse deposition time is 1 to 100 minutes.

8. The grain boundary diffusion method according to claim 1, characterized in that: The heavy rare earth alloy target material S4) has a composition of RE x (Ho a Tm 1-a ) y M 1-x-y , wherein RE is one or more combinations of Dy, Tb, and Gd, M is one or more combinations of Fe, Al, Ga, and Cu, 0≤a≤0.1at.%, and 0.5≤x≤0.9at.%, is 0≤y≤0.1at.%.

9. The grain boundary diffusion method according to claim 1, characterized in that: The coercive force increase of the high-performance sintered NdFeB magnet treated by the grain boundary diffusion method is not less than 12 kOe, and the squareness is not less than 0.

95.

10. A high performance sintered NdFeB magnet, characterized in that: The high performance sintered NdFeB magnet is prepared by the grain boundary diffusion method as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid diffusion process with capability of improving performances of Nd-Fe-B magnet

    CN104505247A

  • Method for improving grain boundary diffusion of sintered NdFeB through loading of nano-film

    CN112750611A

  • Method for preparing high-coercivity sintered neodymium-iron-boron magnet through grain boundary diffusion

    CN112927921A

  • Method for improving binding force of ultra-thick and heavy rare earth coating on surface of sintered neodymium-iron-boron magnet

    CN115620979A

  • Preparation method of sintered neodymium-iron-boron grain boundary diffusion magnet

    CN117012536A

Cited By

  • Ultrahigh-coercivity sintered neodymium-iron-boron magnet and preparation method thereof

    CN121528741A

  • An ultra-high coercivity sintered neodymium-iron-boron magnet and a method of making the same

    CN121528741B

  • La pre-doped high-cerium neodymium-iron-boron magnet and grain boundary diffusion preparation method

    CN121839337A